PSYCHORELIGIOUS THERAPY INCREASE SELF-ESTEEM OF LUPUS SURVIVORS AT KUPU PARAHITA INDONESIA FOUNDATION - Elvira Sari Dewi; Heriberta Tabita Marta Dewi; Ayu Widia Kusuma; Suryanto Suryanto; Nurul Evi; Ridhoyanti Hidayah (Universitas Brawijaya, 2021)
Lupus is a disease of thousand faces with various clinical manifestations and can interfere survivor's appearance, activity, and life. It can cause an inability to realize the strengths and positives that survivors have. This study's aim was to determine the psychoreligious therapy effect on the self-esteem of lupus survivors at Kupu Parahita Indonesia Foundation. The method used was quasi-experimental without a control group with One-group pretest-posttest design on 16 lupus survivors at Kupu Parahita Indonesia Foundation, selected by simple random sampling according to inclusion and exclusion criteria. Respondents were given psychoreligious therapy videos for a month, every weekend with 4 videos in total. We measured theÂ respondentâ€™s self-esteem using the Rosenberg Self-Esteem Scale (RSES) which was translated into Indonesian before and after therapy (Cronbach alpha=0.7, validity=0.422-0.63). The results showed that mean of pre-test score was 27.44, the post-test was 31.94, and the data were normally distributed (p>0.05). The results of the paired T-test showed a significant difference between the pre-test and post-test scores (p=0.000). In conclusion, the administration of psychoreligious therapy increases the self-esteem of lupus survivors at Kupu Parahita Indonesia Foundation.